A systematic approach for analysis and characterization of mispairing in bispecific antibodies with asymmetric architecture. Issue 8 (17th November 2018) - Wang, Chunlei; Vemulapalli, Bhargavi; Cao, Mingyan; Gadre, Dhanesh; Wang, Jihong; Hunter, Alan; Wang, Xiangyang; Liu, Dengfeng
ABSTRACT: Immunoglobulin G–like bispecific antibodies with asymmetric architecture are among the most widely used bispecific antibody formats for diagnostic and therapeutic applications. The primary technical challenge for this format is how to achieve correctly paired assembly of four unique polypeptide chains. Advances in protein engineering and process development are being used to overcome these challenges and are driving a corresponding demand for sensitive analytical tools to monitor and control mispaired species. Here, we report a systematic approach for analysis and characterization of mispairing in asymmetric bispecific antibodies. This approach consists of three orthogonal components, the first of which is a liquid chromatography (LC)-mass spectrometry (MS)–based method to measure the mass of intact antibodies. This method is used for fast analysis of mispairing and requires minimal method development, which makes it an ideal choice for early-stage development. The second component is a hydrophobic interaction chromatography (HIC)–based mispairing method that is suitable for lot release testing. The HIC method is robust and quality control friendly, and offers great linearity, precision, and accuracy. The third component is a two-dimensional LC-MS method for on-line chromatographic peak identification, which not only expedites this task but also reduces the risk of undesirable modifications during conventional fraction collection. These three methods dovetail to form the foundation of a complementary toolbox for analysis and characterization of mispairing in asymmetric bispecific antibodies and provide guidance and support for process development throughout the drug development life cycle.